A fully polynomial parameterized algorithm for counting the number of reachable vertices in a digraph - Ohsaka, Naoto (Information processing letters, 2021)
•We give an FPT algorithm for counting the number of reachable vertices in a digraph.•Our algorithm runs in truly subquadratic time if the feedback edge number is O(n13−ϵ).•The same result holds for vertex-weighted digraphs. We consider the problem of counting the number of vertices reachable from each vertex in a digraph G, which is equal to computing all the out-degrees of the transitive closure of G. The current (theoretically) fastest algorithms run in quadratic time; however, Borassi has shown that this problem is not solvable in truly subquadratic time unless the Strong Exponential Time Hypothesis fails [Borassi, 2016 [13]]. In this paper, we present an O(f3n)-time exact algorithm, where n is the number of vertices in G and f is the feedback edge number of G. Our algorithm thus runs in truly subquadratic time for digraphs of f=O(n13−ϵ) for any ϵ>0, i.e., the number of edges is n plus O(n13−ϵ), and is fully polynomial fixed parameter tractable, the notion of which was first introduced by Fomin et al. (2018) [22]. We also show that the same result holds for vertex-weighted digraphs, where the task is to compute the total weights of vertices reachable from each vertex.